Efficacy of Sodium Tripolyphosphate and Non-Phosphate Additives on the survival of Vibrio parahaemolyticus on Prawns (Fenneropenaeus indicus) (H. Milne-Edwards, 1837) during Frozen Storage - Bini, Francis; Sudha, Santha; Hatha, A. M. (Fishery Technology, 2017)
Use of sodium tripolyphosphate (STPP) and nonphosphateadditives (NP1) in combination withsodium chloride is practised in soaking to preventdrip loss while thawing the frozen shrimp. In thepresent study, we have determined the efficacy ofthese additives on the survival ofVibrio parahaemolyticus on prawns (Fenneropenaeusindicus), during block freezing and individual quickfreezing conditions. Freshly harvested prawns werebeheaded and treated with a blend solution containingSTPP/NP1 at 3 g 100 ml-1 in combination withsodium chloride at 2g 100 ml-1, in two separateexperiments. At appropriate time intervals, wholeprawns were sampled and dilutions plated ontoTCBS agar medium to determine the number of V.parahaemolyticus. Experiments were performed intriplicate. Results indicated that STPP treatedsamples exhibited significant (p